The Effect of Talking Stick Type Cooperative Learning Model Used by Question Card Media on Student Learning Outcomes - Khatimah, Husnul; Rizzaludin, Rizzaludin; Nurjannah, Nurjannah; Sumiyati, Sumiyati; Puspita, Nurul; Hestin, Hestin; Lende, Pendi (Jurnal Ilmiah Mandala Education (JIME), 2026)
This research is motivated by the lack of variety in learning models; only using conventional learning models so that student learning outcomes are less than optimal. The researcher offers the application of a new learning model, namely the talking stick type cooperative learning model. The talking stick type cooperative learning model is a learning model that uses small study groups where students work together to achieve learning goals with the help of a stick, where the stick is used as a tool to determine which students will answer the questions given later. Question card media is a simple media in the form of a card containing questions, where these questions will be answered by students in the learning process. The purpose of this study was to determine the effect of the talking stick type cooperative learning model assisted by question card media on student learning outcomes. This research method uses a pre-experimental research method with a quantitative approach and uses a one group pretest-posttest design research design. Data collection techniques used in this study were tests and documentation. Data analysis techniques in this study include normality tests using Shapiro Wilk with pretest significance results of 0.098 and posttest 0.110 test results more than 0.05 significance then the sample data is normally distributed and homogeneity tests with pretest and posttest significance results of 0.945 test results more than 0.05 significance then the sample data is homogeneous. Data were analyzed using the T test (One Sample T test) with a significance level of 0.000 <0.005 and using the N-Gain test with a mean Ngain score value = 0.46 then the results are interpreted as moderate and at Ngain percent (%) = 46.36 then the results are interpreted as less effective. So, there is an influence of the talking stick type cooperative learning model assisted by question card media in learning social sciences on the learning outcomes of VIII class students of SMP Negeri 1 Dompu, so it can be concluded that Ha is accepted and H0 is rejected.